Mixed Oxides of Iron and Manganese as Potential Low‐Cost Oxygen Carriers for Chemical Looping Combustion. Issue 8 (17th June 2015) - Mungse, Pallavi; Saravanan, Govindachetty; Rayalu, Sadhana; Labhsetwar, Nitin
Abstract Low‐cost oxygen carriers with multicycle chemical looping combustion (CLC) performance and CO2 selectivity have been explored to realize a practical oxygen carrier to obtain sequestration‐ready CO2 from the combustion processes. The cubic structures of the pure mixed oxides of Fe and Mn (Fe3Mn3O8 and FeMnO3; Fe–Mn–O) were prepared successfully as oxygen carriers through a coprecipitation method. The Fe–Mn–O systems showed 100 % CH4 combustion performance in the absence of air or oxygen. MnO and Fe3O4 are the reduced products of the Fe–Mn–O systems after the CH4 combustion reaction. The regeneration of the Fe–Mn–O phase was achieved readily by reoxidation of their reduced products in air. The Fe–Mn–O systems showed a stable and multicycle CLC performance, however, the individual oxides of Fe and Mn showed an inferior CLC performance. Pure CO2 was formed during the CH4 combustion reaction of the Fe–Mn–O systems with practically no toxic CO byproduct. Therefore, the mixed oxide phase of Fe and Mn shows potential as a practical oxygen carrier in terms of its multicycle CLC performance and CO2 selectivity.